CMB polarimetry from the Antarctic Plateau - BOELLA, GIULIANO FILIPPO; DE LUCIA, ANTONIO; GERVASI, MASSIMO; GROSSETTI, GIOVANNI FRANCESCO; PASSERINI, ANDREA; SIRONI, GIORGIO; TARTARI, ANDREA; ZANNONI, MARIO (E D P SCIENCES, 2005)
The Milano Polarimeter (MiPol), a correlation system with phase modulation has been built for the studies of the CMB polarization at large angular scales. At present the system is at the Testa Grigia Observatory on the Italian Alps (3480 m asl). We are ready to bring it to Dome Concordia for observations during the Antarctic winter beginning in March 2006. We discuss the system performance, its sensitivity and the status of the searches for CMB polarization.